Case Study Of Business Excellence Model In Siemens Melaka - Tye, Goh Kok (2000)
This project paper is to examine the core competencies, competitive advantages and business excellence model of Siemens. The study is focused on the continuous improvement program, quality management and TQM organisation culture.